FERMENTASI LIMBAH SEKAM PADI UNTUK PUPUK ORGANIK DALAM BUDIDAYA UDANG VANAME DI KABUPATEN KONAWE SELATAN, PROVINSI SULAWESI TENGGARA - Munier, Muhammad Taswin; Riani, Irdam; Idris, Muhammad; Jali, Wa; Budianto, Budianto; Nur, Andi Irwan; Ramli, Muhammad (Bina Bahari, 2025)
This study investigates the implementation of rice husk waste fermentation for organic fertilizer production in Vaname shrimp cultivation in Konawe Selatan, Southeast Sulawesi. The research evaluates the effectiveness of converting rice husk waste into organic fertilizer through a community-based intervention involving 62 shrimp farming families. The findings demonstrate significant improvements in farmers' knowledge and skills regarding organic fertilizer production, resulting in enhanced soil quality and reduced production costs. The study contributes to sustainable aquaculture practices while addressing environmental concerns associated with traditional farming methods.